Análise da comunicação não verbal mãe-filho na vigência do HIV materno em ambiente experimental - Paiva, Simone de Sousa (2007)
Like all development crisis, pregnancy provokes an unbalance in a person’s life cycle. For an HIV-positive woman, specific aspects of seropositivity add to the unbalance caused by the birth of a child. Thus, there are many factors affecting the relationship between an HIV-positive mother and her child. Non-verbal communication may be the predominant means of communication in mother-child interaction. This study aims at analyzing non-verbal mother-child communication in HIV maternal presence in an experimental environment. It’s a descriptive- investigative study, developed with five binomials of HIV- positive mothers and it was carried out at the Nursery Department of the Laboratory of Health Communication during the second semester of 2007. Videotaping was used as the main data collection resource. Each mother was videotaped once, performing the five main maternal activities: dressing and undressing the child, bathing, playing, feeding and lulling. Videos were analyzed by two evaluators every thirty seconds, completing an observation plan form based on aspects related to non-verbal communication and the attachment theory. Data was analyzed with adequate statistical tests. Analysis was confronted with each binomial’s life history. Some aspects related to seropositivity that affected mother-child non-verbal communication were observed, such as recent seropositivity diagnosis, discrimination suffered due to being HIV-positive, scolding freight in child care and the desire of looking after the child whose diagnosis is still uncertain using other non-verbal stimuli to compensate for the child’s lack of contact with the mother’s breast. Videotaping in a simulated environment may have affected mother behavior during child care. As for non-verbal communication during child care, it was verified that playing is the most interactive mother-child activity, in which various communicative signs, mainly started by the mother, are predominant as a means to stimulate the small child in skill development and to evaluate him/her for early detection of any abnormality that might suggest HIV seropositivity.